The Use of Social Media as an Alternative Learning Medium at SMA Negeri 10 Kaur (Pentagon) - Susidawati Susidawati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Social media can be used as a learning medium that can make a positive contribution in the field of education, especially as a learning medium. To improve the quality, efficiency and effectiveness of learning at SMA Negeri 10 Kaur (Pentagon), it is necessary to analyze the use of social media as an alternative learning medium. This study aims to find out how the use of social media as a learning medium at SMA Negeri 10 Kaur (Pentagon). This research is library research, which studies various reference books and similar previous research results that are useful for obtaining a theoretical basis on the problem under study. Many social networking sites can be used to urge the effectiveness of upgrading and improve student learning outcomes. Some of these social media include YouTube, Facebook, Instagram, and WhatsApp. Based on field facts that SMA Negeri 10 Kaur (Pentagon) has not managed and utilized social media in learning activities. Learning activities are still carried out conventionally, even though the use of social media as a learning medium is an alternative effort for schools and teachers to enrich, strengthen and add to existing learning media so that learning can be more effective and efficient so that student learning outcomes can be improved. The use of social media in the process of teaching and learning activities can also be done in a hybrid manner, which combines or combines online learning with face-to-face learning. On the other hand, SMA Negeri 10 Kaur (Pentagon) already has good facilities and internet connection. All students already have HP devices that can access social media. Based on the literature research above, it can be concluded that the application of upgrading tools with social tool platforms in upgrading can be efficiently used and can improve students' skills to master modules and connect them with everyday life. Therefore, it can be said that the results of practicing students can increase through the application of learning tools with social tool platforms, not only that, students feel captivated and more active to practice. Not only that, this tool also helps in increasing teacher creativity, student activities and independent duty skills in dismantling problems.